The Influence of Social Media (Tiktok) on Public Speaking Mastery of Students of the Communication Science Department Hang Tuah University Pekanbaru - Rahman, Rudi (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Social media is a new trend that can provide extensive knowledge to every user. One example is the TikTok application. This application can provide various education for its users, such as mastery of public speaking. This research is experimental research using a One Group Pretest Posttest Design. Where this research aims to see the influence of the TikTok application on the mastery of public speaking of 11 students majoring in Hang Tuah University, Pekanbaru, who are the subjects of this research. The data analysis technique uses the Wilcoxon test with the help of the SPSS for Windows version 22.00 program. The instrument used is an observation sheet that refers to public speaking indicators, namely pronunciation and intonation, voice volume, fluency, relationship and accuracy of content to topic, gestures, and mimicry. The results of the Wilcoxon test showed that Zscore = 4.370> 0.135 and Asymp. Sig (2 tailed) is 0.000> 0.05 so Ha is accepted and Ho is rejected. Based on these statistical tests, it can be concluded that there is an influence of TikTok social media on the public speaking mastery of students at the Communication Science Department, Hang Tuah University, Pekanbaru. This is also supported by the increase that occurred in the pre-test and posttest results, which were initially 46.91 in the Fair category to 76.63 in the Good category